Intrabeam Radiation Inhibits Proliferation, Migration, and Invasiveness and Promotes Apoptosis of MCF-7 Breast Cancer Cells - Pan, Lingxiao (Technol Cancer Res Treat, 2019)
Intraoperative radiotherapy differs from the more commonly used external beam radiation with respect to fractionation, radiation energy, dose rate, and target volume, which may influence the irradiated cells in a complex manner. However, experimental studies of intraoperative radiotherapy are limited. Intrabeam is a frequently used intraoperative radiotherapy device; we evaluated its effects on the proliferation, apoptosis, migration, and invasion of MCF-7 human breast cancer cells. We performed colony formation assays for cells irradiated with single radiation doses of 0 to 16 Gy. Other cells were irradiated with single radiation doses of 0 to 6 Gy and then continued to be cultured. We measured cell-cycle distributions and apoptosis rates 24 hours later, using flow cytometry, and performed wound-healing assays, Transwell tests, and terminal deoxynucleotidyl transferase–mediated 2′-deoxyuridine 5′-triphosphate nick-end labeling staining 4 weeks later. Colony formation assays showed no positive colonies from cells irradiated with doses of ≥6 Gy. In flow cytometry, the experimental groups had higher late-apoptosis/necrosis rates (P < .01) and higher percentages of cells arrested in G(1) phase (P < .01). Experimental groups also had much lower scratch-repair rates in the wound healing assay (P < .001) and higher apoptosis rates in the terminal deoxynucleotidyl transferase–mediated 2′-deoxyuridine 5′-triphosphate nick-end labeling assay (P < .05). In Transwell tests, the 4 Gy and 6 Gy groups had fewer invading cells than the control group (P < .05). Single-dose irradiation of 6 Gy with the Intrabeam device can effectively inhibit proliferation, migration, and invasiveness and promote apoptosis in MCF-7 cells with long-lasting effects.